Measurement of charged particle spectra in minimum-bias events from proton–proton collisions at s√=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
Pseudorapidity, transverse momentum, and multiplicity distributions are measured in the pseudorapidity range |η| < 2.4 for charged particles with transverse momenta satisfying pT > 0.5 GeV in proton–proton collisions at a center-of-mass energy of √s = 13 TeV. Measurements are presented in three different event categories. The most inclusive of the categories corresponds to an inelastic pp data set, while the other two categories are exclusive subsets of the inelastic sample that are either enhanced or depleted in single diffractive dissociation events. The measurements are compared to predictions from Monte Carlo event generators used to describe high-energy hadronic interactions in collider and cosmic-ray physics.